Clinical implications and prognostic value of mastoid effusion in the management of aneurysmal subarachnoid hemorrhage - Kim, Junhyung; Kim, Sohyun; Jang, Chang Ki; Han, Hyun Jin; Park, Keun Young; Kim, Jung-Jae; Kim, Yong Bae; Oh, Jiwoong (Frontiers in Neurology, 2025)
BackgroundThe clinical significance of mastoid effusion (ME) in intensive care unit (ICU) patients has not been well elucidated. Recently, an association between ME and intracranial pressure (ICP) has been reported. We aimed to investigate the clinical implications of ME occurrence in the management of aneurysmal subarachnoid hemorrhage (aSAH) patients and its association with their prognosis.MethodsData from patients aged > 18 years who were treated for aSAH in a single institution between January 2020 and December 2022 were retrospectively reviewed. Brain CT or MRI images obtained within the first 14 days after the onset of SAH were evaluated for the presence of ME, which is defined as either opacification or an air-fluid level in the mastoid air cells. We examined the patients’ demographic information, neurological and medical status at admission, aneurysm and treatment characteristics, and clinical outcomes. We then analyzed how these factors were associated with the occurrence of ME.ResultsA total of 114 patients were included in the study. ME was observed in 40 patients (34.5%) within the first 14 days, occurring at a mean of 5.0 ± 3.5 days after the onset of SAH. In multivariate analysis, patients with ME were found to have a higher incidence of tracheostomy (odds ratio [OR] 10.034, p = 0.024), radiologic vasospasm (OR 4.987, p = 0.018), a higher APACHE II score (OR 1.138, p = 0.013), and poor clinical outcomes (OR 4.289, p = 0.041), defined as modified Rankin Scale score > 2 at 90 days. Poor clinical outcomes were independently associated with ME (OR 5.003, p = 0.006).ConclusionThis study demonstrated that ME was observed in 34.5% of aSAH patients and was associated with poor clinical outcomes. ME may serve as a simple and useful prognostic indicator for predicting poor outcomes in aSAH patients.